Pengenalan Zat Aditif Pada Makanan Di SDN Purwosari 3 - Widyaningrum, Diyah Ayu; Prasmala, Erfitra Rezqi; Qomariyah, Ismi Nurul (Jurnal ABDINUS : Jurnal Pengabdian Nusantara, 2020)
Food additives or food additives were ingredients that were added intentionally to food in small quantities, with the aimed of improving appearance, taste, texture, flavor and extending shelf life. The students at SDN Purwosari 3 as a whole have the habit of buying snacks at the school gate during school breaks. Snacks sold at the gate include soft drinks, snacks (snacks), and pentol (cilok). Though excessive used of additives could be dangerous to health. So the purpose of this service program was to introduce students at SDN Purwosari 3 regarding food additives. The method used includeed the preliminary, implementation and final stages. Evaluation of the success of the program through a questionnaire. Overall students have gained good knowledge of additives, students have been able sorted and choose snacks, students have reduced the habit of snacks outside of school, and students were diligent in bringing supplies to school. The conclusion of this service program was that Purwosari III Elementary School students were already familiar with food additives.